The Implementation of the BCCT Block Center Learning Model to Enhance Early Childhood Cognitive Development: A Case Study at TKIT 1 Qurrota A’yun Ponorogo - Aulia, Rifqi (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Abstract: This study aims to describe the preparation, implementation, and effectiveness of the Beyond Center and Circle Time (BCCT) block centre learning model in enhancing the cognitive development of early childhood students at TKIT 1 Qurrota A’yun, Ponorogo. Using a qualitative case study approach, data were collected through participant observation, interviews, and document analysis. The results indicate that teacher preparation, including lesson planning and learning environment organisation, aligns with BCCT principles. Applying the block centre model effectively fostered cognitive abilities such as problem-solving, early mathematical logic, and spatial understanding. However, limitations in space and some students’ uneven progress suggest room for improvement in infrastructure and teaching methods. This study highlights the importance of teacher training and infrastructure development to optimise the BCCT model further. Future research should explore how enhancing facilities can improve learning outcomes in diverse educational settings. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan persiapan, pelaksanaan, dan efektivitas model pembelajaran sentra balok berbasis Beyond Center and Circle Time (BCCT) dalam meningkatkan perkembangan kognitif anak usia dini di TKIT 1 Qurrota A’yun, Ponorogo. Dengan menggunakan pendekatan studi kasus kualitatif, data dikumpulkan melalui observasi partisipan, wawancara, dan analisis dokumen. Hasil penelitian menunjukkan bahwa persiapan guru, termasuk perencanaan pembelajaran dan pengorganisasian lingkungan belajar, sudah sesuai dengan prinsip BCCT. Penerapan model sentra balok terbukti efektif dalam mengembangkan kemampuan kognitif seperti pemecahan masalah, logika matematika awal, dan pemahaman spasial. Namun, keterbatasan ruang dan perkembangan siswa yang tidak merata menunjukkan adanya ruang untuk perbaikan dalam infrastruktur dan metode pengajaran. Penelitian ini menekankan pentingnya pelatihan guru dan pengembangan infrastruktur untuk lebih mengoptimalkan model BCCT. Penelitian selanjutnya harus mengeksplorasi bagaimana peningkatan fasilitas dapat menghasilkan hasil pembelajaran yang lebih baik dalam berbagai lingkungan pendidikan.